Profil PROFIL KETERAMPILAN TEKNOLOGI INFORMASI DAN KOMUNIKASI GURU SEKOLAH DASAR DALAM IMPLEMENTASI KURIKULUM MERDEKA DI BANYUWANGI - Solipyani; Sunardi; Farizi, Imam (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study describes teachers' information and communication technology (ICT) skills in implementing the Merdeka Curriculum at Gugus 3 Yosomulyo, Gambiran District, Banyuwangi Regency. The Merdeka Curriculum requires the integration of technology in the learning process, making ICT skills a crucial aspect for teachers. In particular, the integration with the Merdeka Mengajar platform necessitates competencies in operating computers, using software applications, and utilizing the internet and educational websites. This study employs a qualitative descriptive method with the Miles and Huberman approach, which consists of data reduction, data presentation, and conclusion drawing. Data were collected through questionnaires, interviews, and observations involving six teachers from three schools in Gugus 3 Yosomulyo. The findings indicate that most teachers possess strong ICT skills in various aspects, which are considered adequate to support the implementation of the Merdeka Curriculum in elementary schools. This study is expected to serve as a reference for the professional development of teachers in utilizing ICT in schools.